2016
DOI: 10.18034/gdeb.v5i1.124
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction of the Employees of the General Insurance Companies in Bangladesh

Abstract: This study investigates the employees' job satisfaction of general insurance companies in Bangladesh. A questionnaire was utilized to collect primary data from both public and private general insurance companies. The first part of the questionnaire comprises of the demographic profile of the respondents and the last part indicates the key measuring variables on a Likert scale ranging from 5 (strongly agree) to 1 (strongly disagree) of job satisfaction. The total number of respondents for this study was 385. 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Ahmed (2015) revealed that recruitment & selection, training & development, salary & benefits, and reward have a positive effect on employees' job satisfaction whereas supervisory role and job security have an adverse effect. Uddin et al (2016) conducted a study on the employees of the general insurance companies in Bangladesh and found that pay and promotional potential, well-organized chain of command and general working condition have positive relationship with job satisfaction where poor team spirit and poor job security have negative relation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmed (2015) revealed that recruitment & selection, training & development, salary & benefits, and reward have a positive effect on employees' job satisfaction whereas supervisory role and job security have an adverse effect. Uddin et al (2016) conducted a study on the employees of the general insurance companies in Bangladesh and found that pay and promotional potential, well-organized chain of command and general working condition have positive relationship with job satisfaction where poor team spirit and poor job security have negative relation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most complicated topics, job satisfaction, includes a wide range of emotions and circumstances. Job satisfaction at work is influenced by compensation, motivation, an efficient chain of command, and general working circumstances (Uddin et al 2016;Bilge et al 2021). Employee work happiness is affected by wages, benefits, and motivation since they are frequently cited as two of the top three elements affecting employee job satisfaction (Society for Human Resource Management 2012).…”
Section: Compensation Employee Motivation and Employee Satisfactionmentioning
confidence: 99%
“…There are few studies about the factors that affect job satisfaction among them is the pay, promotion, work environment, team spirit, job security, corporate image, and supervisor's expertise, collaborative, professional development, job rotation, communication effectiveness, leadership, motivation, training and empowerment [20], [21], [22], which are done then taken several solutions for improving job satisfaction of employees with training, and empowerment.…”
Section: Introductionmentioning
confidence: 99%